Association of Thyroid-Stimulating Hormone (TSH) Levels With the Prognosis of Patients Undergoing Heart Transplantation: A Retrospective Study - Wei, Jiajie; Zhou, Yingsheng (Frontiers in Cardiovascular Medicine, 2021)
To investigate the impact of TSH levels using a more stringent cutoff of subclinical hypothyroidism (i.e., TSH >2.5 mIU/L) on the short-term complications and long-term prognosis in patients who underwent heart transplantation (HTx).